A new species of the genus Rhopalaea (Class: Ascidiacea) from the Red Sea - Shenkar, Noa (Zootaxa, 2013)
During regular surveys and collection of ascidians along the Red Sea coast of Israel, several specimens of an undescribed species of Rhopalaea were collected. Samples were collected by SCUBA from the natural coral reef and man-made structures at depths between 10 to 40m. This is the first species of the genus Rhopalaea described from the Red Sea, which is characterized by a transparent, uncolored gelatinous tunic with elongated attachment extensions, and is distinguished by its eight atrial lobes, thoracic muscle arrangement, and branchial sac structure.